Coagulation abnormalities in Ehrlichia canis-infected dogs and detection and dynamics of anti-platelet antibodies in thrombocytopenic dogs - Shropshire, Sarah, author; Lappin, Michael, advisor; Dow, Steve, committee member; Olver, Christine, committee member; Webb, Craig, committee member; Ames, Marisa, committee member (Colorado State University. Libraries, 2018)
Vector-borne diseases affect millions of people and domestic animals worldwide resulting in significant morbidity and mortality rates. In dogs, vector-borne diseases such as Ehrlichia canis can cause a myriad of clinical signs (lethargy, weight loss, and epistaxis) and hematological abnormalities (hyperglobulinemia, thrombocytopenia, and anemia). It has been previously reported that E. canis results in systemic inflammation and vasculitis as well as the formation of immunoglobulin associated platelets or anti-platelet antibodies. It has been theorized that anti-platelet antibodies can deleteriously affect platelet function and if concurrent significant thrombocytopenia is present, signs of bleeding may manifest. However, anti-platelet antibodies and thrombocytopenia can occur in a variety of disease processes in the dog including other vector-borne diseases, neoplasia, and idiopathic primary immune syndromes. Thrombocytopenia is also one of the most common acquired hemostatic abnormality observed in dogs. Consequently, determining the underlying cause and mechanism for thrombocytopenia in dogs can represent a frequent diagnostic challenge. Additionally, inflammation is often present in dogs with thrombocytopenia due to various causes. Inflammation and immune system processes directly affect hemostasis which can lead to derangements in the coagulation system resulting in clinical signs of bleeding or thrombosis. The goals of the research described in this dissertation were to investigate the dynamic changes of anti-platelet antibodies in thrombocytopenic dogs and the changes that occur in the coagulation system during a vector-borne infection such as E. canis in dogs.
Keywords: Ehrlichia canis; thrombocytopenia; whole blood impedance platelet aggregometry; flow cytometry; coagulation; thromboelastography